An Embodied Cyberlearning Platform for Gestural Interaction with Cross‐Cutting Science Concepts. Issue 1 (25th February 2019) - Lindgren, Robb; Morphew, Jason; Kang, Jina; Junokas, Michael
ABSTRACT: Research from brain science and the learning sciences support the notion that human cognition is grounded in our sensorimotor engagement with the physical world and that processes of learning can be shaped by our movements and actions. Increasing recognition that effective educational interventions can be seeded with embodied actions is paralleled by recent and rapid advances in sensing and motion capture technologies. These advances allow for a new wave of cyberlearning environments that permit learners to use their bodies to create and manipulate digital representations of core ideas in a variety of learning domains. Drawing on the research literature on embodied cognition and design principles for creating effective embodied educational simulations, we present the design of a cyberlearning platform called ELASTIC 3 S. We describe the design rationale and preliminary data from a small empirical study of the ELASTIC 3 S platform that address the potential for enhancing science, technology, engineering, and mathematics (STEM) learning and engagement through embodied interaction.